Unravelling cysteine-deficiency-associated rapid weight loss - Alan Varghese; Ivan Gusarov; Begoña Gamallo-Lana; Daria Dolgonos; Yatin Mankan; Ilya Shamovsky; Mydia Phan; Rebecca Jones; Maria Gomez-Jenkins; Eileen White; Rui Wang; Drew R. Jones; et al. (Nature, 2025)
Abstract Around 40% of the US population and 1 in 6 individuals worldwide have obesity, with the incidence surging globally 1,2 . Various dietary interventions, including carbohydrate, fat and, more recently, amino acid restriction, have been explored to combat this epidemic 3–6 . Here we investigated the impact of removing individual amino acids on the weight profiles of mice. We show that conditional cysteine restriction resulted in the most substantial weight loss when compared to essential amino acid restriction, amounting to 30% within 1 week, which was readily reversed. We found that cysteine deficiency activated the integrated stress response and oxidative stress response, which amplify each other, leading to the induction of GDF15 and FGF21, partly explaining the phenotype 7–9 . Notably, we observed lower levels of tissue coenzyme A (CoA), which has been considered to be extremely stable 10 , resulting in reduced mitochondrial functionality and metabolic rewiring. This results in energetically inefficient anaerobic glycolysis and defective tricarboxylic acid cycle, with sustained urinary excretion of pyruvate, orotate, citrate, α-ketoglutarate, nitrogen-rich compounds and amino acids. In summary, our investigation reveals that cysteine restriction, by depleting GSH and CoA, exerts a maximal impact on weight loss, metabolism and stress signalling compared with other amino acid restrictions. These findings suggest strategies for addressing a range of metabolic diseases and the growing obesity crisis.